Influence of Ca/Al Ratio on Properties of Amorphous/Nanocrystalline Cu–Al–Ca–O Thin Films. Issue 1 (26th September 2014) - Huang, Bo‐Wei; Wen, Cheng‐Yen; Lin, Guan‐Wei; Chen, Po‐Yuan; Jiang, Yu‐Hao; Kao, Peng‐Kai; Chi, Chu‐Te; Chang, Hung; Cheng, I‐Chun; Chen, Jian‐Zhang; Paranthaman, P.
<x xml:space="preserve">Abstract</x> This article reports the characterization of thin films sputtered from CuAl1−xCaxO targets (x = 0, 0.05, 0.1, 0.15, and 0.2) at room temperature. All films exhibit amorphous/nanocrystalline structures. Their transparency increases slightly with the addition of Ca. Furthermore, the resistivity decreases as the Ca/Al atomic ratio increases. Transmission electron microscopy with energy dispersive spectroscopy mapping indicates that the composition is uniform throughout the films deposited from the highest Ca doping concentration target. Some nanocrystals are present at the top surface of the CuAl0.8Ca0.2O thin film as well as the interface region between the CuAl0.8Ca0.2O thin film and the glass substrate, whereas the interior of the film is pretty amorphous with some embedded nanocrystals. X‐ray photoelectron spectroscopy shows that the Cu2+/Cu+ atomic ratio increases with the Ca/Al atomic ratio, indicating the enhancement of p‐type conductivity from the nonisovalent Cu–O alloying.